2019
DOI: 10.21203/rs.2.15849/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal healthcare services use in Mwanza Region, Tanzania: A cross-sectional baseline survey

Abstract: Background Improving maternal health by reducing maternal morbidity and mortality relates to Goal 3 of the Sustainable Development Goals. Achieving this goal is supported by antenatal care (ANC), health facility delivery, and postpartum care. This study aimed to understand levels of use and correlates of uptake of maternal healthcare services among women of reproductive age (15–49 years) in Mwanza Region, Tanzania.Methods A cross-sectional multi-stage sampling household survey was conducted to obtain data from… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
2
6
2
Order By: Relevance
“…Figures 1 and 2 show the analysis results in line with the findings in several previous studies that showed a strong positive relationship between antenatal care and delivery performed in healthcare [15][16][17] . The complete antenatal care performed during pregnancy, the more likely it is to deliver delivery to healthcare 18 .…”
Section: Resultssupporting
confidence: 86%
“…Figures 1 and 2 show the analysis results in line with the findings in several previous studies that showed a strong positive relationship between antenatal care and delivery performed in healthcare [15][16][17] . The complete antenatal care performed during pregnancy, the more likely it is to deliver delivery to healthcare 18 .…”
Section: Resultssupporting
confidence: 86%
“…However, this nding was lower than studies conducted in Holeta Town (87.1%)[18], Addis Ababa(97.6%) [11], Ethiopia and Kiambu, Kenya (91.73%) [19], Tanzania (96%) [20], and India (83%) [21]. This observed difference might be because of variation in residence.…”
Section: Factors Associated With Institutional Deliverycontrasting
confidence: 57%
“…Kaloleni and Rabai are coastal sub-counties in Kilifi County with a population of 304, 778; 52.6% health facility deliveries and 52.3% skilled birth attendance [14]. Mwanza region lies in the northern part of Tanzania and has a population of 2,772,509 people; 57.2% of the women attending at least four ANC visits and 75.3% hospital delivery [29]. The two countries and the regions within the countries were chosen due to their high maternal mortality [14,15].…”
Section: Study Design and Settingmentioning
confidence: 99%